The squat bible : the ultimate guide to mastering the squat and finding your true strength - Horschig, Aaron, ....-; Sonthana, Kevin, ....-; Neff, Travis, ....- ([s.l.] : Squat University, 2016)
As a physical therapist, coach, and certified strength and conditioning specialist, Dr. Aaron Horschig began to notice the same patterns in athletes over and over. Many of them seemed to pushed themselves as athletes in the same ways they push themselves out in the real world. Living in a performance-based society, Dr. Horschig saw many athletes who seemed to not only want to be bigger and stronger but to get there faster. This mentality ultimately led to injuries and setbacks, preventing athletes from reaching their full potential. Now, after developing unique and easy-to-use techniques on how to train and move well, Dr. Horschig shares his invaluable insights with readers in The Squat Bible: The Ultimate Guide to Mastering the Squat and Finding Your True Strength. This detailed plan enables you to unearth the various weak spots within your body—the areas that leave you in pain and hinder your ability to perform—and completely change your approach to athleticism. Discover new strength, new power, and astounding potential you never knew you possessed. As the founder of SquatUniversity.com, Dr. Horschig knows that when you transform the way you work out, you transform your body—and your life.
Keywords: Krachttraining